AR Integration in Chemical Bonding Learning: Challenges and Opportunities - Dita Novita Rini; Eli Rohaeti; Suyanta (Universitas Pendidikan Ganesha, 2025)
Learning chemical bonds at the secondary school level often faces challenges due to the abstract nature of the material and its difficulty in visualizing. This study aims to analyze the main challenges in learning chemical bonds and explore opportunities for integrating Augmented Reality (AR) technology as an innovative learning medium. This study used a qualitative descriptive approach. The subjects in this study consisted of 64 11th-grade students and two chemistry teachers. The population was selected purposively, while the sample was selected using a random sampling method. Data were collected through classroom observations, student questionnaires, and semi-structured interviews with teachers. The data obtained were analyzed qualitatively and descriptively. The results showed that 90% of students exhibited a passive attitude during the learning process, and 60% had not achieved mastery of the learning. Students struggled to understand Lewis structures, bond types, and molecular shapes. As many as 78% of students expressed interest in technology-based learning media, especially those that support three-dimensional visualization. Teachers also cited media limitations as a significant obstacle in explaining microscopic concepts. This study concludes that learning chemical bonds still faces significant challenges related to student engagement and the complexity of the abstract material. The research suggests that the development of AR-based Student Worksheets (LKPD) can enhance learning engagement and help students develop more concrete mental representations of complex chemical bonding concepts.